LipoBots: Using Liposomal Vesicles as Protective Shell of Urease‐Based Nanomotors. (14th August 2020) - Hortelão, Ana C.; García‐Jimeno, Sonia; Cano‐Sarabia, Mary; Patiño, Tania; Maspoch, Daniel; Sanchez, Samuel
Abstract: Developing self‐powered nanomotors made of biocompatible and functional components is of paramount importance in future biomedical applications. Herein, the functional features of LipoBots (LBs) composed of a liposomal carrier containing urease enzymes for propulsion, including their protective properties against acidic conditions and their on‐demand triggered activation, are reported. Given the functional nature of liposomes, enzymes can be either encapsulated or coated on the surface of the vesicles. The influence of the location of urease on motion dynamics is first studied, finding that the surface‐urease LBs undergo self‐propulsion whereas the encapsulated‐urease LBs do not. However, adding a percolating agent present in the bile salts to the encapsulated‐urease LBs triggers active motion. Moreover, it is found that when both types of nanomotors are exposed to a medium of similar pH found in the stomach, the surface‐urease LBs lose activity and motion capabilities, while the encapsulated‐urease LBs retain activity and mobility. The results for the protection enzyme activity through encapsulation within liposomes and in situ triggering of the motion of LBs upon exposure to bile salts may open new avenues for the use of liposome‐based nanomotors in drug delivery, for example, in the gastrointestinal tract, where bile salts are naturally present in the intestine. Abstract : Enzyme‐powered nanomotors are designed by attaching or encapsulating urease onto or into liposomes, which act as a nanomotor chassis and protective shell for urease. The propulsion of nanomotors encapsulating urease is triggered by a percolating agent present in the bile salts. Moreover, enzyme encapsulation on the inner liposomal compartment allows preservation of functionality when the nanomotors are exposed to harsh conditions.